Progesterone administration in aborting bovines: An etiology of fetal maceration - KUMAR, PRAVESH; SHARMA, VIVEK; SHARMA, AKSHAY; SINGH, MADHUMEET; ANANYA, ANANYA (The Indian Journal of Animal Sciences, 2021)
The aim of the present study was to assess the effect of progesterone administration in aborting animals as the veterinarians/para-veterinarians very often use progesterone to prevent ensued abortion in cows and buffaloes. It is suggested that the use of progesterone should be avoided in aborting animals once its process has set in.